2020
DOI: 10.1021/acsbiomaterials.0c00450
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-Rich 13X Zeolite as a Filler with Remineralizing Potential for Dental Composites

Abstract: A zeolite with high ion-exchange potential was used as an active filler with remineralizing potential in composites that can be applied in restorative dentistry. Two calcium-rich forms of the 13X zeolite were obtained by sodium to calcium ion exchange and mineralization of a hydroxyapatite layer. These fillers were also silanized and mixed with methacrylic resins and photoinitiators to obtain composite materials. First, the effectiveness of the filler preparation and silanization was confirmed by X-ray diffrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 60 publications
(106 reference statements)
0
21
0
Order By: Relevance
“…Researchers have previously added different fillers in the adhesives to study their mechanical properties and bond strength. These fillers included calcium-rich zeolite [ 9 ], hydroxyapatite (HA) [ 10 ], and graphene oxide (GO) [ 11 ]. These studies have revealed that the incorporation of inorganic fillers leads to an improvement of mechanical properties of the adhesive, remineralization potential, and increased bond strength [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have previously added different fillers in the adhesives to study their mechanical properties and bond strength. These fillers included calcium-rich zeolite [ 9 ], hydroxyapatite (HA) [ 10 ], and graphene oxide (GO) [ 11 ]. These studies have revealed that the incorporation of inorganic fillers leads to an improvement of mechanical properties of the adhesive, remineralization potential, and increased bond strength [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The DA establishes a direct connection with the tooth surface; therefore, its inclusion inside the adhesive could be more beneficial than its incorporation in the composite resin [6]. Researchers have incorporated various nanoinorganic fillers inside the DA, as they expand mechanical properties, remineralization competence, and the bond strength of dental resin composites [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the absorption peak at 460 cm −1 is attributed to T-O bending vibration. The peak at 753 cm −1 is connected with the symmetric stretching vibration of Si (Al)-O in the Si-O-Al framework [ 31 , 37 ]. All the characteristic bands of ZC are similar to ZP.…”
Section: Resultsmentioning
confidence: 99%